2007
DOI: 10.1007/s10573-007-0008-3
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized components of energetic systems: Structure, thermal behavior, and combustion

Abstract: Ultrafine and nanosized powders of oxidizers and metals are considered as promising ingredients for the development of new highly effective solid rocket propellants. An ultrafine ammonium perchlorate (AP) powder and nanosized aluminum were produced by mechanical activation and investigated using electron and atomic force microscopy and X-ray powder and thermal analyses. It is shown that the activation energy of nanoaluminum oxidation is considerably lower than that for the micron-size powder, and the activatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 5 publications
0
17
0
Order By: Relevance
“…Many different mechanisms have been proposed to explain the combustion behavior of Al nanoparticles (Al-NPs). [16][17][18][19] By adding Al-NPs into micron size particles, numerous experiments have observed the enhanced oxidation reactivity in terms of burning rate, 20,21 flame speed, 22,23 activation energy, 24 ignition sensitivity, 23,[25][26][27] combustion velocity, 25 and agglomeration. 3 Nanosize Al particles have lower melting temperatures than that of micron size particles, because of large surface-to-volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Many different mechanisms have been proposed to explain the combustion behavior of Al nanoparticles (Al-NPs). [16][17][18][19] By adding Al-NPs into micron size particles, numerous experiments have observed the enhanced oxidation reactivity in terms of burning rate, 20,21 flame speed, 22,23 activation energy, 24 ignition sensitivity, 23,[25][26][27] combustion velocity, 25 and agglomeration. 3 Nanosize Al particles have lower melting temperatures than that of micron size particles, because of large surface-to-volume ratio.…”
Section: Introductionmentioning
confidence: 99%
“…The structure, combustion and application of energetic systems based on fine, submicron and nanosized metals (in addition to changes in the names of these materials with time) were investigated extensively by the author's group [38,[152][153][154][155][156][157], as well as by other teams of researchers [158][159][160][161][162][163][164]. The most prominent result observed was the decrease in the ignition time and increase in the burning rate for compositions containing nano-Al [38,155,156].…”
Section: Energetic Inks For Rms: Composition and Componentsmentioning
confidence: 99%
“…The structure, combustion and application of energetic systems based on fine, submicron and nanosized metals (in addition to changes in the names of these materials with time) were investigated extensively by the author's group [38,[152][153][154][155][156][157], as well as by other teams of researchers [158][159][160][161][162][163][164]. The most prominent result observed was the decrease in the ignition time and increase in the burning rate for compositions containing nano-Al [38,155,156]. However, the wide utilization of nanometals is limited by several factors, i. e., (i) the reduced metal content and associated performance losses [160] (note the surprising positive effect of the oxide layer [165]), (ii) stability issues, e. g., oxidation during storage [166], (iii) coalescence prior to reaction, diminishing the effects of nanosize [167,168], (iv) the gradual increase in viscosity for compositions with a binder [169], and (v) the difficulty of obtaining a uniform composite mixture with nanocomponents [156,170].…”
Section: Energetic Inks For Rms: Composition and Componentsmentioning
confidence: 99%
“…Recently, many investigators have confirmed that using nanodispersive aluminum powder noticeably improved the operational and physical characteristics of rocket fuels [6][7][8]. Consequently, it can be supposed that the addition of nanodispersive powdered aluminum borides into HEC will also improve the performance of these compositions through the increase in the rate and efficiency of combustion of these components.…”
Section: Introductionmentioning
confidence: 99%